Timing of Quaternary geomagnetic reversals and excursions in volcanic and sedimentary archives. (15th January 2020) - Channell, J.E.T.; Singer, B.S.; Jicha, B.R.
Abstract: We review the ages of Quaternary magnetic polarity reversals and magnetic excursions. Improvements in radioisotopic 40 Ar/ 39 Ar dating of reversals and excursions reflect the use of multi-collector mass spectrometers, along with ultra-low backgrounds, laser-based incremental heating methods, and adoption of 28.201 Ma for the Fish Canyon sanidine (FCs) standard age (Kuiper et al., 2008). These improvements have brought 40 Ar/ 39 Ar ages of reversals and excursions into close correspondence with astrochronological ages based on the correlation of δ 18 O data to LR04 (Lisiecki and Raymo, 2005) and, in a few cases, correlation to ice-core chronologies. Ages of two polarity reversals, the Matuyama-Brunhes boundary and base Olduvai, are at odds with ages given in popular geomagnetic polarity timescales. Sedimentary records of the Laschamp and Iceland Basin excursion are numerous and widespread, and attest to global manifestation and global synchronicity of these excursions. Records of other Quaternary excursions are less numerous. The Blake excursion (∼115 ka) has been recorded in North Atlantic sediments, Chinese loess, Indian Ocean volcanics, and Spanish speleothems. The Santa Rosa excursion (∼932 ka) has been recorded in North Atlantic and Phillipine Basin sediments, as well as in volcanic rocks from New Mexico and Galapagos. The Punaruu excursion (∼1115 ka) has been observed in sediments from the North Atlantic and California Margin as well as in volcanic rocks on Tahiti. Uniformity of individual excursion ages, using astrochronological, 40 Ar/ 39 Ar and U–Th methods, argues for synchronous global manifestation of excursions, strengthening the usefulness of magnetic excursions (and reversals) in Quaternary stratigraphy. Highlights: Review of ages of Quaternary magnetic reversals and excursions. Approaching uniformity for 40 Ar/ 39 Ar, astrochronological and ice-core chronologies. Existing data ague from synchronous global manifestation of reversals and excursions. Well-dated excursions are short-lived "golden spikes" for Quaternary stratigraphy.